2011
DOI: 10.1007/s10869-011-9234-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Inter-Role Conflict on Proactive Individual’s Experience of Burnout

Abstract: Purpose This study examined how proactive personality interacts with inter-role conflict, measured as work-family conflict and family-work conflict, to predict burnout, measured as emotional exhaustion, depersonalization, and reduced personal accomplishment. Design/Methodology/Approach Participants were 171 clerical employees. Hierarchical multiple regression was used to test whether proactive personality moderated the relationship between inter-role conflict and forms of burnout. Findings Family-work conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 74 publications
5
54
0
Order By: Relevance
“…These mean the employees of CPA firms in Indonesia are not emotionally exhausted because of their job, even though their family demands make it difficult for them to perform their job. This result is similar to the study by Jawahar et al (2012) and Zhang et al (2012) which also failed to provide evidence of a significant relationship between FIW and emotional exhaustion. Zhang et al (2012), therefore, argued that only excessive job demands could largely generate emotional exhaustion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These mean the employees of CPA firms in Indonesia are not emotionally exhausted because of their job, even though their family demands make it difficult for them to perform their job. This result is similar to the study by Jawahar et al (2012) and Zhang et al (2012) which also failed to provide evidence of a significant relationship between FIW and emotional exhaustion. Zhang et al (2012), therefore, argued that only excessive job demands could largely generate emotional exhaustion.…”
Section: Discussionsupporting
confidence: 89%
“…Stress occurs when individuals forfeit resources or are faced with the threat of losing resources. Jawahar et al (2012) agreed that individuals have limited resources and a negative effect (exhaustion) may result from an individuals' failure to fulfill his/her personal responsibilities at work and home. When individuals experience excessive demands in the workplace, they probably lose more resources (time, energy, attention) for their family.…”
Section: The Relationship Between Workfamily Conflict and Emotional Ementioning
confidence: 99%
“…For example, experiences of conflict between work and family have been associated with emotional exhaustion and depression (Jawahar, Kisamore, Stone, & Rahn, 2012; Van Steenbergen, Ellemers, & Mooijaart, 2007), and higher negative work-family spillover has been linked with worse self-reported overall physical health, a greater number of physical health symptoms (Amstad et al, 2011), musculoskeletal pain (Kim et al, 2014), a greater likelihood of obesity (Grzywacz, 2000), and more sleep problems (Crain et al, in press). Although most research assessing the link between spillover and health used cross-sectional data, one longitudinal study found that an increase in negative work-family spillover over four years was associated with greater depressive symptoms, poorer physical health, and a greater likelihood of hypertension diagnosis (Frone, Russell, & Cooper, 1997).…”
Section: Negative and Positive Work-family Spillover And Healthmentioning
confidence: 99%
“…For example characteristics of work interfering with family and characteristics of family interfering with work causes depression, stress, exhaustion, anxiety, low satisfaction from marriage, poor role performance, low professional well-being, life dissatisfaction, low organizational commitment, work dissatisfaction, burnout (Eby, Casper, Lockwood, Bordeaux & Brinley, 2005;Frone et al, 1992;Frone, Russell & Cooper, 1997;Jennifer, Kisamore, Stone & Rahn, 2012;Maertz & Boyar, 2011;Willis et al, 2008).…”
Section: Work-family Conflictmentioning
confidence: 99%